The Impact of Technology Mastery on Employee Turnover with Technostress as the Moderator - Ayumi Ayumi; Monika Palupi Murniati (Soegijapranata Catholic University, 2024)
Employee turnover in Indonesia has a fairly high rate and some of this is due to technology. On the other hand, 66% of companies are switching to digital transformation. This causes the employee turnover rate to increase. Most companies will experience an increase in employee turnover if there is technostress in their workforce. This research aims to examine the moderating effect of technostress on the relationship between technology mastery and employee turnover. The research model was built based on the employee perspective. Primary data was collected through questionnaires given to 151 workers or employees in Semarang City. Hypothesis testing is carried out using linear regression and moderated regression analysis (MRA). The research results show that there is a negative relationship between technology mastery and employee turnover, as well as the moderating role of technostress which influences the influence of technology mastery on employee turnover. This research helps company owners and human resource management to reduce employee turnover rates and can be used as a consideration for company evaluation to reduce technostress. To the best of the researchers' knowledge, this study has never been explored before. This research shows how these three variables act synergistically in a model.